The Gambia : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2007)
This Selected Issues paper assesses The Gambia's external competitiveness by reviewing developments in several indicators, ranging from exchange rate-based indices to survey-based assessments of the investment climate. The paper reviews the evolution of several multilateral and bilateral real exchange rate indices for The Gambia, and summarizes the results of a regression analysis that tests for misalignment of the exchange rate. The paper also evaluates the degree of autonomy extended to the Central Bank of The Gambia (CBG) under the provisions of the new Central Bank of The Gambia Act, 2005.